1D morning glory-like calixarene-based coordination polymers as a support for Au/Ag nanoparticles. (7th July 2017) - Wang, Shentang; Hang, Xinxin; Zhu, Xiaofei; Han, Haitao; Zhang, Guoshuai; Liao, Wuping
Graphical abstract: Two 1D morning glory-like calixarene-based coordination polymers have been obtained by solvothermal reactions, which can act as a support for the fabrication of Au and Ag nanoparticles. The silver composite shows high performance in the heterogeneous catalytic reduction of 4-nitrophenol. Abstract: Two 1D calixarene-based coordination polymers, namely [M3 (TC4A-SO2 )(SSA)(CH3 OH)2 (H2 O)] (M = Co, CIAC-218 and M = Ni, CIAC-219 ; H4 TC4A-SO2  =  p - tert -butylsulfonylcalix[4]arene, H2 SSA = 5-sulfosalicylic acid), were synthesized under solvothermal conditions and structurally characterized by elemental analysis, IR spectroscopy and single-crystal X-ray diffraction analysis.CIAC-218 acts as a support for the fabrication of Au and Ag nanoparticles. The silver composite shows high performance in the heterogeneous catalytic reduction of 4-nitrophenol, which follows a first order reaction with a rate constant of 0.32 min −1 . TheAg/CIAC-218 catalysts were easily recovered for reuse.